Development of three vignette types of selected constitutive antinomies of social work: a study of the development and comparison of text, video and VR vignettes - Averbeck, Felix; Utesch, Till (Frontiers in Education, 2025)
In social work, constitutive antinomies represent permanent tensions in practice that can only be addressed reflexively in teaching. In order to convey these, a direct transfer from theory to practice is necessary, which is presented, among other things, in the form of vignettes (hypothetical situations for teaching and research based on real cases). The present study examines three types of vignettes in order to ascertain the most beneficial teaching approach for social work: 1. Text vignettes are written descriptions of hypothetical situations. 2. Video vignettes offer a standardized perspective on the situation, presented in the format of a film. 3. Virtual reality (VR) vignettes allow viewers to select their own perspective within a 360° video, thereby providing a realistic representation of the situation. The results are compared based on the dispersion of the target and actual states of the vignettes, their practical relevance, explicitness, presence experience and flow experience. Within a randomized control group design (text n = 55, video n = 54, VR n = 53), three main hypotheses on the added value of VR vignettes were investigated in comparison to the comparison group of video vignettes and the control group of text vignettes. The results show that VR vignettes enhance the theory-practice transfer. This is partly because they have better content validity and a higher immersion experience than text and video vignettes.